Redefining WILD syndrome: a primary lymphatic dysplasia with congenital multisegmental lymphoedema, cutaneous lymphovascular malformation, CD4 lymphopaenia and warts. Issue 1 (16th December 2021) - Mansour, Sahar; Josephs, Katherine S; Ostergaard, Pia; Gordon, Kristiana; Van Zanten, Malou; Pearce, Julian; Jeffery, Steve; Keeley, Vaughan; Riches, Katie; Kreuter, Alexander; Wieland, Ulrike; Hägerling, René; et al.
Abstract : Background: Primary lymphoedema (PL) syndromes are increasingly recognised as presentations of complex genetic disease, with at least 20 identified causative genes. Recognition of clinical patterns is key to diagnosis, research and therapeutics. The defining criteria for one such clinical syndrome, 'WILD syndrome' (W arts, I mmunodeficiency, L ymphoedema and anogenital D ysplasia), have previously depended on a single case report. Methods and results: We present 21 patients (including the first described case) with similar clinical and immunological phenotypes. All had PL affecting multiple segments, with systemic involvement (intestinal lymphangiectasia/pleural or pericardial effusions) in 70% (n=14/20). Most (n=20, 95%) had a distinctive cutaneous lymphovascular malformation on the upper anterior chest wall. Some (n=10, 48%) also had hyperpigmented lesions resembling epidermal naevi (but probably lymphatic in origin). Warts were common (n=17, 81%) and often refractory. In contrast to the previous case report, anogenital dysplasia was uncommon—only found in two further cases (total n=3, 14%). Low CD4 counts and CD4:CD8 ratios typified the syndrome (17 of 19, 89%), but monocyte counts were universally normal, unlike GATA2 deficiency. Conclusion: WILD syndrome is a previously unrecognised, underdiagnosed generalised PL syndrome. Based on this case series, we redefine WILD as 'W arts, I mmunodeficiency, andL ymphatic D ysplasia' and suggest specific diagnostic criteria. The essential criterion is congenital multisegmental PL in a 'mosaic' distribution. The major diagnostic features are recurrent warts, cutaneous lymphovascular malformations, systemic involvement (lymphatic dysplasia), genital swelling and CD4 lymphopaenia with normal monocyte counts. The absence of family history suggests a sporadic condition, and the random distribution of swelling implicates mosaic postzygotic mutation as the cause.